2018
DOI: 10.3168/jds.2017-12813
|View full text |Cite
|
Sign up to set email alerts
|

Predicting manure volatile solid output of lactating dairy cows

Abstract: Organic matter (OM) in livestock manure consisting of biodegradable and nonbiodegradable fractions is known as volatile solids (VS). According to the Intergovernmental Panel on Climate Change (IPCC) Tier 2 guidelines, methane produced by stored manure is determined based on VS. However, only biodegradable OM generates methane production. Therefore, estimates of biodegradable VS (dVS; dVS = VS - lignin) would yield better estimates of methane emissions from manure. The objective of the study was to develop math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…An increase in DMI without change in OM digestibility would result in an increase in the amount of VS excreted. Other studies reported a positive relationship between OM intake and VS excretion (Hassanat et al, 2013;Massé et al, 2016;Appuhamy et al, 2018).…”
Section: Chemical Composition Of the Mixture Of Feces And Urinementioning
confidence: 88%
“…An increase in DMI without change in OM digestibility would result in an increase in the amount of VS excreted. Other studies reported a positive relationship between OM intake and VS excretion (Hassanat et al, 2013;Massé et al, 2016;Appuhamy et al, 2018).…”
Section: Chemical Composition Of the Mixture Of Feces And Urinementioning
confidence: 88%
“…Such an evaluation requires a realistic and detailed representation of the cow's complex digestive processes. Several empirical models have been developed to predict output and composition of feces and urine (e.g., Reed et al, 2014;Appuhamy et al, 2018), but such models do not allow for detailed manure characterization and do not reflect the availability of N from urinary and fecal components for subsequent losses or use by plants.…”
Section: Introductionmentioning
confidence: 99%
“…Average nutrients by month and cow class were estimated using a weighted average, to account for different percent contributions to each diet. Monthly manure emissions were then estimated following Appuhamy et al [55] by first calculating volatile solid excretion (VS; kg month −1 ) of all cattle on farm. Volatile solids are biodegradable and nonbiodegradable fractions of organic matter in manure [55].…”
Section: Cattle Emissionsmentioning
confidence: 99%
“…Monthly manure emissions were then estimated following Appuhamy et al [55] by first calculating volatile solid excretion (VS; kg month −1 ) of all cattle on farm. Volatile solids are biodegradable and nonbiodegradable fractions of organic matter in manure [55]. Monthly VS was calculated as a function of nutritional intake (Table 2):…”
Section: Cattle Emissionsmentioning
confidence: 99%